2007
DOI: 10.1111/j.1460-9568.2007.05698.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of initiation factors controlling protein synthesis on cultured astrocytes in lactic acid‐induced stress

Abstract: The goals of this work were first to assess whether the lactic acidosis observed in vivo in ischemia may by itself explain the inhibition of protein synthesis described in the literature and second to study the factors controlling the initiation of protein synthesis under lactic acid stress. Primary rat astrocyte cultures exposed to pH 5.25 underwent cell death and a strong inhibition of protein synthesis assessed by [3H]methionine incorporation, which was solely due to acidity of the extracellular medium and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…This is consistent with induced HIF-1α protein accumulation under hypoxia. Extreme acidity (pH=5.5) can lead to eIF2α phosphorylation and translation inhibition in astrocytes (37). eIF2α phosphorylation has also been shown to regulate the protein levels of HIF-1α (38).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with induced HIF-1α protein accumulation under hypoxia. Extreme acidity (pH=5.5) can lead to eIF2α phosphorylation and translation inhibition in astrocytes (37). eIF2α phosphorylation has also been shown to regulate the protein levels of HIF-1α (38).…”
Section: Discussionmentioning
confidence: 99%
“…Vantelon et al reported that exposure of astrocytes to 16 mM lactate did not alter protein synthesis and at pH values below 6, protein synthesis was decreased [20]. In addition, in the presence of lactic acid a strong and sustained phosphorylation of the eukaryotic initiation factor 2α (eIF2α), the central regulator of the ER stress response, was reported [20].…”
Section: Discussionmentioning
confidence: 99%
“…2 may suggest that the activity of PKR is less important in the proliferation of mesothelioma under acidic condition. Acidic conditions, in fact, enhanced the phosphorylation of eIF2, but this was confirmed at pH lower than 5.5 and not over 6.2 in a partially PKR-independent manner (Vantelon et al, 2007). So the phosphorylation of eIF2 without PKR at pH 6.7 might not cause this PKR independency at pH 6.7.…”
Section: Pkr Inhibitormentioning
confidence: 91%